Oil extracted from spent coffee grounds for bio-hydrotreated diesel production. (15th October 2016) - Phimsen, Songphon; Kiatkittipong, Worapon; Yamada, Hiroshi; Tagawa, Tomohiko; Kiatkittipong, Kunlanan; Laosiripojana, Navadol; Assabumrungrat, Suttichai
Graphical abstract: Highlights: The spent coffee oil with high FFAs was hydrotreated to liquid biofuel. Pd/C gave higher olefins while NiMo/γ-Al2 O3 gave higher isoparaffins liquid products. The diesel fuel fraction can have a cetane number as high as 80. The physiochemical properties of diesel fraction comply with commercial standard. Abstract: Oil extracted from spent coffee grounds is utilized as a renewable source for bio-hydrotreated fuel production. In the present work, oil yield up to 13% can be obtained by Soxhlet extraction with hexane as a solvent. As the extracted oil contained high content of free fatty acids (6.14%), therefore one step alkali-catalyzed for ester based biodiesel production is impractical. Hydrotreating of extracted oil was performed over two catalysts i.e. NiMo/γ-Al2 O3 and Pd/C with different operating parameters i.e. reaction time, operating temperature, and H2 /oil. It was found that the reaction time of 2 h and the reaction temperature of 400 °C are favorable operating conditions. The liquid products mostly consisted of n -pentadecane and n -heptadecane, which contain one carbon atom shorter than the corresponding fatty acid (Cn−1 ) i.e. palmitic and stearic acid, respectively. Unfavorable cracking of diesel product is pronounced at high temperature and prolonged reaction time. In addition, although increased H2 /oil promoted overall reaction and hydrodeoxygenation activity (Cn−1 /Cn decreased) for both catalysts, hydrocracking is enhanced over Pd/C, leading to significant increase in gasoline yield. Moreover, Pd/C gave higher olefin content in liquid product (22.3 wt%) than NiMo/γ-Al2 O3 (4.8 wt%). However, NiMo/γ-Al2 O3 shows higher isomerization activity. The amount of isoparaffins catalyzed by NiMo/γ-Al2 O3 and Pd/C were 10.8 and 1.7 wt%, respectively. Physiochemical analysis of the diesel fraction exhibit satisfactory properties. The density and kinematic viscosity were consistent with the specification of commercial bio-hydrogenated diesel, NExBTL, while the cetane index was much higher than conventional diesel.